A Phenomenology Of Expatriate-Local Interactions In Malaysia - Potter, Adam Evan (2024)
The objective of this study is to understand how expatriate-local interactions (ELI) are experienced for expatriates and Malaysians working in multinational enterprises (MNEs). This thesis contributes original and embodied knowledge of ELI to international human resources management (IHRM) literature and describes the relationship between ELI and the physical body, the role of language and speech in ELI, and the ways in which expatriates and locals experience both positive and negative surprise.